Pantoea agglomerans, Klebsiella pneumoniae, and Shigella flexneri isolated from the Cisadane River as multiresistant bacteria to copper and dyes - Wahyu Irawati; Candra Yulius Tahya; Greisnaningsi Greisnaningsi (Indonesian Journal of Biotechnology, 2022)
Copper pollution in Cisadane is a serious environmental issue that needs to be resolved immediately due to its negative impacts on river ecosystems. Bioremediation utilising indigenous bacteria offers excellent potential to restore copper‐contaminated river water. This study aimed to obtain indigenous copper‐resistant bacteria isolated from the Cisadane River as copper bioremediation agents. Bacteria from Cisadane River water samples were isolated by the spread plate method on Luria Bertani medium containing 3 mM CuSO4. Resistance was determined based on the minimum inhibitory concentration value, while copper concentration was measured using an atomic absorption spec‐ trophotometer. The results presented a total of 13 bacterial isolates with a minimum inhibitory concentration of up to 8 mM CuSO4. Sequence alignment analysis was performed on three selected copper‐resistant bacteria, i.e. isolate IrCis1, IrCis4 and IrCis13, which were identified as Pantoea agglomerans, Klebsiella pneumoniae and Shigella flexneri based on 16S rRNA, respectively. Each isolate accumulated copper at 1.19 mg, 1.34 mg and 0.92 mg/g DW of cells, with copper biosorption potentials of 73.74%, 70.17% and 67.73%, respectively. In conclusion, P. agglomerans strain IrCis1, K. pneu‐ moniae strain IrCis4 and S. flexneri strain IrCis5 isolated from the Cisadane River can be used as copper bioremediation agents.